Chronic pedunculopontine nucleus stimulation restores functional connectivity. - Schweder, P; Joint, C; Hansen, P; Green, A; Quaghebeur, G; Aziz, T (2010)
The mechanisms of deep brain stimulation (DBS) are poorly understood. Earlier, high-frequency DBS has been thought to represent a depolarization block of the target area and low-frequency stimulation has been thought to 'drive' neuronal activity. We investigated the long-term effect of low-frequency DBS in a longitudinal imaging study of a patient who received bilateral pedunculopontine nucleus stimulation. We used the diffusion tensor imaging techniques including probabilistic tractography and topographic mapping to analyze long-term changes in connectivity with low-frequency DBS. Post-DBS connectivity analysis suggested a normalization of pathological pedunculopontine nucleus connectivity with DBS therapy. These findings may help elucidate the mechanisms of DBS, suggesting neuroplasticity involving a reorganization of target connectivity long term. This is the first reported case showing neuroimaging evidence of neuroplasticity after low-frequency DBS.